Fulfillment of Rights to Recovery for Victims of Sexual Violence Which Settlement is Made Outside the Judicial Process in Ternate City - Syafari, Tri; Fathurahim, Fathurrahim; Robo, Basto Daeng (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
It was recorded that in 2022 the number of sexual violence in North Maluku Province reached 285 cases, where this number is considered very worrying because in 2021 there were 144 cases, an increase of 141 cases or almost 100% from the previous year. Research conducted in the city of Ternate as a barometer for North Maluku Province, provides an illustration that fulfilling the right to recovery for victims of sexual violence whose resolution is carried out outside the judicial process. However, the implications of peace can certainly not benefit the victim. This research is a type of juridical-normative research, namely research carried out by examining secondary materials and library materials. The type of approach used is a conceptual approach and a statutory regulatory approach. That the fulfillment of the right to recovery for victims of sexual violence whose resolution was carried out outside the judicial process in Ternate City in the form of handling the 3 cases was carried out peacefully by fulfilling the conditions agreed upon by both parties, namely fulfilling their right to recovery in the form of material rehabilitation in the form of compensation, in this case the perpetrator provided tuition fees. victim. That the implications of peace can certainly not benefit the victim, because in the end the perpetrator was free with a guarantee of compensation given to the victim's family so that the case was not continued. This situation shows that one form of sexual violence has the potential to give rise to other forms of sexual violence, for example rape results in forced marriage for survivors.